Comprehensive municipal programs of development of the consumer market (Путеводитель предпринимателя)
In article the questions connected with development and deployment in practice of a program method of regulation of the trade sphere at municipal level are considered. Features of a program method, expediency of its use are given in the mechanism of local self-government.